Case Report: A New Subtype of Lynch Syndrome Associated With MSH2 c.1024_1026 Identified in a Chinese Family - Li, Lu; Zhao, Zhe; Dong, Lin; Jia, Jia; Su, Ke; Bai, Hua; Wang, Jie (Frontiers in Medicine, 2022)
Background: Lynch syndrome is an autosomal dominant disorder associated with a high incidence of various cancer types. Multiple variants of mismatch repair genes have been reported for Lynch syndrome. However, the diagnosis in patients with atypical cancer types remains challenging. Specifically, little is known about the genetic background of Lynch syndrome-related renal carcinoma. We present a case wherein a renal carcinoma patient with multiple primary skin tumors harbored a variant that has not been previously shown to be associated with Lynch syndrome. Case presentation: The proband was a 60-year-old Chinese man with a history of Lynch syndrome-related renal carcinoma and recurrent primary skin tumors. Immunohistochemistry revealed loss of MSH2 and MSH6. Sequencing of mismatch repair genes revealed a previously unknown germline MSH2 mutation (c.1024_1026), which results in an amino acid deletion (p.V342). This variant was co-segregated among the carcinoma-affected family members. After 6 cycles of immunotherapy, a marked regression of the skin tumors was observed. Conclusions: We clarify the pathogenic significance of this newly described mutation and suggest immunotherapy for patients with this subtype of Lynch syndrome.